Utility of TG/HDL-c ratio as a predictor of mortality and cardiovascular disease in patients with chronic kidney disease undergoing hemodialysis: A systematic review - Gonzáles-Rubianes, Diana Zolans (2022)
The triglyceride/high-density cholesterol-lipoprotein (TG/HDL-c) is a biomarker of cardiovascular events and mortality. In hemodialysis patients, the evidence is controversial. A systematic review was carried out in the Medline, Scopus, Embase, Web of Science, and Pubmed databases to identify the relevant cohort studies on cardiovascular events and mortality in hemodialysis patients the role of TG/HDL-c as a risk factor. Four cohort-type studies were evaluated, with a total of 52,579 hemodialysis patients. Three studies conducted in Asian populations and one study in the United States had the highest percentage of the sample (50,673 patients). The elevated TG/HDL-c ratio is associated with better survival, and there is a consistent gradual inverse association between TG/HDL-c and mortality in all analysis subgroups. In the decile categorization of the exposure variable, a 21% decrease in the risk of cardiovascular mortality and a 15% decrease in all-cause mortality in the highest decile compared to the reference group (D10 aHR = 0.79; 95% CI: 0.69–0.91 and D10 aHR = 0.85; 95%CI: 0.78–0.92). Our results show that the TG/HDL-c ratio is a protective factor for cardiovascular outcomes and mortality in the American population and a risk factor for them in the population from Asia.